Explosion Characteristics and variation of oxidized coal dust - HE Jie; CHENG Kai; ZHANG Jin (Meikuang Anquan, 2023)
Oxidized coal is a coal body that has undergone the process of warming up and cooling down, and has been widely used in mine fire area start-up, stratified mining, and re-mining of residual coal, etc. The coal dust generated from coal development and utilization in these areas is oxidized coal dust. Due to the different degrees of oxidation of the coal body, the internal structure is affected, and the explosion characteristics of the resulting oxidized coal dust are changed. For the non-stick coal, this paper used a programmed heating chamber to pretreat the samples at different temperatures(25 ℃, 75 ℃ and 115 ℃) to explore the change in the explosion characteristics of the oxidized coal dust under the conditions of different variables (oxidized coal dust cloud concentration, oxidized coal dust particle size). The results show that the explosion process of oxidized coal dust can be divided into four stages, namely, the initial negative pressure stage, high pressure dust injection stage, explosion boost stage and pressure decay stage; the explosion characteristics of oxidized coal dust and coal dust concentration conform to the quadratic polynomial law, which increases and then decreases with increasing concentration, and the optimal coal dust concentrations of T25, T75 and T115 coal dust are concentrated at 300 g/m3 and 200 g/m3; in the coal dust cloud concentration is constant, the maximum explosion pressure value of oxidized coal dust decreases with the increase of particle size.